Research and clinical updates on IRAK4 and its roles in inflammation and malignancy: themes and highlights from the 1st symposium on IRAK4 in cancer - Garcia-Manero, Guillermo; Platzbecker, Uwe; Lim, Kian-Huat; Nowakowski, Grzegorz; Abdel-Wahab, Omar; Kantarjian, Hagop; Verma, Amit; Starczynowski, Daniel T. (Frontiers in Hematology, 2024)
The intracellular serine/threonine interleukin 1 receptor-associated kinase 4 (IRAK4) is necessary for most signaling by activated Toll-like receptors (TLRs). Activation of IRAK4 drives activation of nuclear factor kappa B (NF-κB) and so promotes cell survival, inflammation, and other aspects of the adaptive immune response. However, the IRAK4 pathway can be coopted by cancers and lead to the survival and proliferation of malignant cells. Inappropriate IRAK4 activity has been linked with the progression of myelodysplastic syndrome (MDS), other hematologic malignancies, and some solid tumors, and preclinical cancer models indicate that IRAK4 inhibition has anti-tumor effects. As such, inhibition of IRAK4 is an emerging and attractive target for tumor suppression. The growing interest in IRAK4 motivated the 1st Symposium on IRAK4 in Cancer held in October 2022 to bring together IRAK4 researchers and clinicians to discuss new insights into the biology of IRAK4 and development of IRAK4 inhibitors. Presentations and discussions at the meeting provided updates on the biology of IRAK4 and its links with mutations in the spliceosome, new outcomes from preclinical models that indicate synergy between inhibitors of IRAK4 and FLT3 and BTK inhibitors, and an update on the clinical development of the investigational IRAK4 inhibitor emavusertib, currently being assessed in ongoing phase 1/2 clinical studies in hematologic cancers and several solid tumors.